ANALISIS KINERJA CV. FABAMUS FAMILI UTAMA SEMARANG DENGAN BALANCED SCORECARD - Nilla Mega Permata; Hari Susanta Nugraha; Sendhang Nurseto (Universitas Diponegoro, 2014)
A method of measuring the performance of the company to assist in knowing the health condition of the company itself. The study was conducted on the CV. Fabamus First Family with Balanced Scorecard approach to measuring through four perspectives: financial perspective, customer perspective, internal business process perspective and learning and growth perspectives. In the financial aspects of performance measurement with a weight of 70%, 10% customer perspective, internal business process perspective 10% as well as learning and growth perspective 10%. Key Performance Indicators on the financial perspective in the form of profitability, activity, liquidity and the respective weights of 35%, 17.5% and 17.5%. Customer perspective with the customer retention KPI weighting of 4.5% and 5.5% customer satisfaction. Internal business process perspective of service quality KPI 5.5% and 4.5% integration of business processes. Learning and growth perspective with employee training KPI 4% and 6% employee satisfaction.The results obtained, healthcare companies in 2009 to 2010 the average in good condition but the scale balanced scorecard measurement expressed overall performance is still not good. Advice can be given the need for improvements in internal business process perspective and learning and growth perspectives.